Quand un coenseignement interroge la forme scolaire au profit de l’éducation inclusive - Maxime Tant (Recherches en Éducation)
The objective of this study was to better understand in what and how the evolution of co-teaching over a school year between a primary school teacher and a physical education teacher transforms the traditional school form for the benefit of the inclusive education. To do this, participant observations of thirty-two PE sessions and twenty-eight co-planning sessions treated with constant comparative analysis brought out three themes. First, provided that co-teaching is supported by the schools, co-planning is progressively more efficient, promoting the construction of an inclusive class climate. Secondly, provided teachers are compatible and com-plementary, pedagogical remediation is more original in the service of student social participation. Finally, following the construction of work habits between teachers, the forms of co-interventions are more varied for the benefit of students' motor learning.